KEEFEKTIFAN METODE PROBLEM BASED LEARNING DALAM PEMBELAJARAN FIQIH DI PERGURUAN TINGGI - Mulyono (Sekolah Tinggi Agama Islam Hasan Jufri Bawean, 2016)
Problem Based Learning (PBL) method was learning method that teach students for solving the problem and reflecting it with their experiences in order to develop thinking ability in solving problem which was meaningful, relevant, and contextual. PBL was one of methods in contextual teaching and learning based on constructivist learning theory. The result of this paper showed that PBL method was applicable to be implemented in learning fiqh, and it could be combined with other conventional method for achieving advantage of learning result optimally. On the other hand, PBL was effective enough in helping students’ understanding and in linking their education with real problem in society.